A CROSS-SECTIONAL STUDY OF ATTITUDE AMONG MEDICAL STUDENTS ABOUT ONLINE LEARNING DURING COVID-19 PANDEMIC IN SOUTHERN INDIA - RAYAM, SRIHARSHA; MUSADDIQ, SHABNUM; MEEGADA, PURNA PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The study aimed to assess the attitude of the medical students toward online classes during COVID-19 pandemic in Southern India. Methods: This study was an online cross-sectional descriptive study. First- and 2nd-year medical students were asked to fill out an online questionnaire using Google form. The participants were asked to answer the questions on a Likert scale, from 1 to 5. The questionnaire consists of details about the type of gadgets, type of internet connection used for E-learning classes, overall Students’ attitude and satisfaction with online education, and the challenges associated with online teaching. Results: A total of 279 medical students participated, among them 168 (60.2%) were females and 111 (39.8%) were males. About 43.36% of students used mobiles for purpose of E-learning. 59.14% of students expressed their interest to incorporate E-learning into the curriculum in the future. Regarding students’ attitudes and satisfaction with online education, 63.4% stated that easy to access online teaching and 50.15% stated that online teaching was effective, 48.35 stated that online teaching was engaging and visually attractive 45.9% and 38% stated that online teaching was the effective communication method. Major challenges associated with online teaching were lack of cocurricular activities that was 63.5% followed difficulty to concentrate during classes was 58.7%. For plans and criteria for evaluation, 58.06% preferred the objective method of examination. Conclusion: The majority of students showed positive responses toward online teaching during COVID-19 pandemic but there are certain challenges like lack of cocurricular activities and difficulty concentrating during classes.